Body mass index as a determinant in the development of osteoarthritis: A cross-sectional study - Adyasputri, A A I Ayesa Febrinia; Raini, Putu Ayu Meka (PT. Mega Science Indonesia, 2025)
Osteoarthritis (OA) is a degenerative joint disease characterized by the progressive degradation of articular cartilage, the formation of new bone (osteophytes), and changes in synovial and subchondral tissues. These pathological changes contribute to pain, joint stiffness, and functional impairment in OA. The primary risk factors for OA include advanced age and increased body mass index (BMI). This study aimed to determine the association between BMI and the incidence of osteoarthritis. A cross-sectional analytical study was conducted among 70 participants aged >40 years from Banjar Cepaka, Badung, Indonesia, using simple random sampling method. Osteoarthritis severity was assessed using the WOMAC questionnaire, while BMI was calculated from measured height and weight. Chi-square analysis was performed to determine the associations between variables. Osteoarthritis severity assessment using the WOMAC questionnaire demonstrated that 58.6% of the participants experienced severe symptoms, while 27.1% reported moderate symptoms. Chi-square analysis revealed a statistically significant association between BMI and osteoarthritis incidence (p = 0.000). The cross-tabulation showed that individuals with obesity class I had 81.2% severe osteoarthritis cases, while those with obesity class II had 83.3% severe cases and 16.7% very severe cases of osteoarthritis. In conclusion, a strong association between elevated BMI and osteoarthritis severity among adults over 40 years in rural Indonesia. The progressive relationship between increasing body weight and joint degeneration severity underscores the modifiable nature of this risk factor through weight management interventions.